ПРОБЛЕМЫ ТОЖДЕСТВА И РАЗЛИЧИЯ СИНОНИМОВ - Каллибекова, Г.А. (SCIENCE and SOCIETY, 2020)
This article sets the goal of theoretical understanding of the synonymy of the Russian language, the development of skills for understanding and analyzing the meanings of Russian synonyms, mastering such important lexicological concepts as lexical synonymy, synonyms, the difference between synonymous relations from other relations in vocabulary based on the proximity of lexical meanings, such as doublets, identity and differences between synonyms, types of differences between synonyms are semantic, functional-stylistic, emotionally expressive, combinable.